Tongue shaped oropharyngeal teratoma with cleft palate in a neonate: A case report - Samiul Hasan (Journal of Neonatal Surgery, 2021)
Background: Atypical presentation of an atypical abnormality makes the diagnosis challenging. Oropharyngeal teratoma (epignathus) is a rare, potentially life-threatening neonatal tumor. Its atypical presentation may cause a delay in diagnosis and increase morbidity and mortality.